2020
DOI: 10.20517/2347-9264.2019.69
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal wall procedures: the benefits of prehabilitation

Abstract: Prehabilitation for abdominal wall procedures provides an opportunity to further modify patient risk factors for surgical complications. It includes interventions that optimize nutrition, glycemic control, functional status, and utilization of the patient's microbiome pre-, intra-, and postoperatively. Through a multidisciplinary and anticipatory approach to patients' existing co-morbidities, the physiological stress of surgery may be attenuated to ultimately minimize perioperative morbidity in the elective se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 134 publications
(146 reference statements)
0
4
0
Order By: Relevance
“…Previous studies have demonstrated that SSOs occur mainly in patients having a high-risk characteristic at the time of surgery [ 7 – 9 ]. Numerous studies have unambiguously reported that preoperative smoking, obesity, or a low physical activity level influence incisional hernia repair negatively, in terms of SSO and recurrence [ 10 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that SSOs occur mainly in patients having a high-risk characteristic at the time of surgery [ 7 – 9 ]. Numerous studies have unambiguously reported that preoperative smoking, obesity, or a low physical activity level influence incisional hernia repair negatively, in terms of SSO and recurrence [ 10 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Optimization of patient related risk factors requires, in theory, long pre-planning and screening before surgery rendering preoperative optimization extremely difficult for most cases. Scientific interest in “Prehabiliation” programs prior to major abdominal surgery increases of late and first studies show promising results in reducing overall and pulmonary morbidity ( 16 ) but definitive clinical effectiveness is currently very limited ( 17 ), especially regarding wound complications ( 18 , 19 ). Hopefully, in the future, more research in this area will allow further reduction of postoperative wound-related morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…A quality control cycle was initiated by applying the Plan-Do-Check-Act (PDCA) cycle and outcome evaluation at least once a year during a general meeting (65)(66)(67). Finally, a complex hernia care pathway was drafted.…”
Section: Complex Hernia Programmentioning
confidence: 99%
“…After an era of focusing at enhanced recovery after surgery (ERAS), accent shifted several years ago to the preoperative setting (62). Preoperative identification of modifiable risk factors (prehabilitation) enables patient optimization and improves postoperative outcome, also in complex hernia patients (63)(64)(65)(66)(67)(68)(69).…”
Section: Prehabilitationmentioning
confidence: 99%